2019
DOI: 10.1007/s42770-019-00048-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism in association with susceptibility to tuberculosis: a study in a Pakistani population

Abstract: Tuberculosis is becoming a global issue with raising occurrences; particularly in developing countries, the situation is alarming. Besides environmental factors, host genetic factors are vital in disease development. A demographical and genotypic analysis in relation to tuberculosis commencement is conducted in a Pakistani population, and genotypic frequency of EBI3 (rs4740) was analyzed. Allelic frequencies of EBI3 (rs4740) were significantly associated with disease susceptibility in the reviewed population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…[ 5 ] Nowadays, many researchers have studied the field of TB pathogenesis at the genetic level, such as single nucleotide polymorphisms. [ 6 , 7 ] However, key genes associated with TB have not been reported until now. Thus, our study uses online bioinformatics data to explore differentially expressed genes (DEGs) between TB and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Nowadays, many researchers have studied the field of TB pathogenesis at the genetic level, such as single nucleotide polymorphisms. [ 6 , 7 ] However, key genes associated with TB have not been reported until now. Thus, our study uses online bioinformatics data to explore differentially expressed genes (DEGs) between TB and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Expression profiling by array plays an important role in the field of molecular biology and it can simultaneously detect thousands of genes [5] . Nowadays, many researchers have studied the field of TB pathogenesis at the genetic level, such as single nucleotide polymorphisms [6,7] . However, key genes associated with TB have not been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…The organism is an aerobic pathogenic bacterium that typically causes respiratory infection. TB displays epidemic cycles that might, rarely, last for centuries [1].…”
Section: Introductionmentioning
confidence: 99%
“…This implied that IL-35 was closely involved in the pathogenesis of PTB; hence, it was very necessary to explore the relationship between IL-3 5 gene variation and PTB genetic susceptibility. Previous studies found that the IL-3 5 rs4740 variant showed a significant relationship with a decreased risk for PTB ( 30 ), while the rs568408 variant was not related to PTB risk ( 31 ). Nevertheless, our study found no significant association between rs2243123, rs2243135, rs568408, rs428253, rs4740, and rs9807813 variants in the IL-35 gene and PTB susceptibility.…”
Section: Discussionmentioning
confidence: 97%